2012
DOI: 10.1158/0008-5472.can-11-2663
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Signatures Associate with Pathogenesis and Progression of Osteosarcoma

Abstract: Osteosarcoma remains a leading cause of cancer death in adolescents. Treatment paradigms and survival rates have not improved in two decades. Driving the lack of therapeutic inroads, the molecular etiology of osteosarcoma remains elusive. MicroRNAs (miRNAs) have demonstrated far-reaching effects on the cellular biology of development and cancer. Their role in osteosarcomagenesis remains largely unexplored. Here we identify for the first time an miRNA signature reflecting the pathogenesis of osteosarcoma from s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
359
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(382 citation statements)
references
References 45 publications
(51 reference statements)
22
359
0
1
Order By: Relevance
“…Most patients with osteosarcoma are diagnosed at a late stage, and many patients need radiotherapy or/and chemotherapy 5, 6, 7, 8. However, the response to chemotherapy is usually poor in these patients 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with osteosarcoma are diagnosed at a late stage, and many patients need radiotherapy or/and chemotherapy 5, 6, 7, 8. However, the response to chemotherapy is usually poor in these patients 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Normal chondrocytes, chondrosarcoma, and osteosarcoma have been shown to express miRNA-181a [1,2,6,9]. The current study has made an important contribution in terms of how it demonstrates a pathogenic role for miR181a, particularly in terms of the upregulation of VEGF, and how it may respond to hypoxia in chondrosarcoma cells.…”
Section: Where Do We Need To Go?mentioning
confidence: 70%
“…Previous studies [1,2,6,9] demonstrated that miRNA-181a is neither cell nor tumor specific. Normal chondrocytes, chondrosarcoma, and osteosarcoma have been shown to express miRNA-181a [1,2,6,9].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 Given the profound effect that regulated miRNA expression has on bone marrow cell differentiation and activity, it is perhaps not surprising that misregulation of miRNAs has also been linked to a number of bone-related pathologies, including miRNAs as biomarkers for bone metastasis progression A Aleč ković and Y Kang [36][37][38] and osteosarcoma. [39][40][41][42][43] Importantly, misregulated miRNAs have been proposed as potential biomarkers of the specific bone-related diseases as they may accurately reflect the disease state of the bone. Because osteoporosis is caused by an imbalance between bone formation and resorption, misregulated bone marrow miRNAs represent promising indicators of assessment of bone fragility and provide potential therapeutic options to restore homeostasis.…”
Section: Mirna Regulation In Bone Homeostasismentioning
confidence: 99%